Familial hypocalciuric hypercalcaemia and acute pancreatitis. - Davies, M (1981)
Four families with familial hypocalciuric hypercalcaemia were studied. The probands presented with abdominal pain, which in three was due to acute pancreatitis; in two the condition was life threatening. Serum concentrations of calcium, magnesium, phosphate, and immunoassayable parathyroid hormone, urinary calcium excretion, and the rate of renal tubular reabsorption of phosphate were measured; the findings were compared with results in 10 patients with primary hyperparathyroidism matched for serum calcium concentration to establish differences between the diseases. Familial hypocalciuric hypercalcaemia should be suspected in patients with hypercalcaemia in whom daily urinary calcium excretion is below 5 mmol (200 mg) provided renal insufficiency, vitamin D deficiency, and ingestion of drugs that reduce calcium excretion have been excluded. Most cases appear to run a benign course, but some may suffer considerable morbidity. Surgical treatment should be reserved for patients with severe complications, when all parathyroid tissue should be removed.